Ethos Kerja Santri (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
This research is to find out the influence of parents educational pattern and pesantren milieu for santris ethos. To analyze data is used univaried and bivaried method. Santris ethos from the two pesantren is relatively low. The writer showed that there is no signfficant relationship between parentâs educational pattern and santris ethos. Although there rs the positive relationship, but it is low. The writer explained that santris ethos based on pesantren milieu. Modern pesantren milieu that applies discipline and sanction rigidly is not giving positive impact. It is important for them to practical behavior before graduated from pesantren.